2020
DOI: 10.28925/2663-4023.2020.9.4558
|View full text |Cite
|
Sign up to set email alerts
|

Clustering Network Attack Features in Information Security Analysis Tasks

Abstract: The paper proposes an algorithm with self-learning elements for intrusion detection systems, as well as an improved clustering technique which is recorded by the data system concerning information security events. The proposed approaches differ from those known using an entropy approach allowing data to be presented as homogeneous groups, moreover, each such group (or cluster) may correspond to predetermined parameters. The proposed solutions relate to the possibilities of assessing dynamic dependencies betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Other studies by researchers [10][11] have shown the effectiveness of data clustering methods in timely detecting anomalies in the functioning of critical infrastructure.…”
Section: Methods Of Cyber Protection Of Critical Infrastructure Objectsmentioning
confidence: 99%
“…Other studies by researchers [10][11] have shown the effectiveness of data clustering methods in timely detecting anomalies in the functioning of critical infrastructure.…”
Section: Methods Of Cyber Protection Of Critical Infrastructure Objectsmentioning
confidence: 99%